The prevalence and correlates of unintended pregnancy among female sex workers in South China: a cross-sectional study - Liang, Peng; Zhao, Peizhen; Shi, Yijia; Huang, Shujie; Wang, Cheng (Reproductive health, 2024)
Female sex workers (FSW) are particularly vulnerable to unintended pregnancy. Research examining the experience of unintended pregnancy due to commercial sex among Chinese FSW, however, is limited. This study aimed to examine the prevalence and correlates of unintended pregnancy due to commercial sex among FSW in China. In 2021, a cross-sectional study was conducted among 1257 FSW in five cities from Guangdong provinces in South China. Data were collected on social-demographic characteristics, sexual behaviors, experience of unintended pregnancy due to commercial sex and its pregnancy outcome, as well as experience of abortion in lifetime. Multivariable logistic regression analysis was employed to identify factors associated with unintended pregnancy. Among the 1257 FSW, 19.3% reported having at least one unintended pregnancy due to commercial sex. Of those, 96.7% chose to terminate the pregnancy through induced abortion, and 40.5% reported undergoing multiple induced abortions in their lifetime. Multivariable logistic regression indicated that FSW working in current location over one year (adjusted Odds Ratio (aOR): 2.82, 95% CI 1.71-4.64) and having more than seven clients in the past week (aOR: 4.53, 95% CI 2.74-7.51) were more likely to have had unintended pregnancy due to commercial sex. Working in high tier (aOR: 0.21, 95% CI 0.14-0.30) and consistent condom use with clients in the past month (aOR: 0.16, 95% CI 0.10-0.23) were associated with a lower proportion of FSW having ever had unintended pregnancy. Unintended pregnancy are prevalent among FSW in South China. Interventions aimed at reducing the prevalence of unintended pregnancy and enhancing post-abortion care could be necessary among Chinese FSW.